Evolution and function of eukaryotic‐like proteins from sponge symbionts. Issue 20 (12th September 2016) - Reynolds, David; Thomas, Torsten
Abstract: Sponges (Porifera) are ancient metazoans that harbour diverse microorganisms, whose symbiotic interactions are essential for the host's health and function. Although symbiosis between bacteria and sponges are ubiquitous, the molecular mechanisms that control these associations are largely unknown. Recent (meta‐) genomic analyses discovered an abundance of genes encoding for eukaryotic‐like proteins (ELPs) in bacterial symbionts from different sponge species. ELPs belonging to the ankyrin repeat (AR) class from a bacterial symbiont of the sponge Cymbastela concentrica were subsequently found to modulate amoebal phagocytosis. This might be a molecular mechanism, by which symbionts can control their interaction with the sponge. In this study, we investigated the evolution and function of ELPs from other classes and from symbionts found in other sponges to better understand the importance of ELPs for bacteria–eukaryote interactions. Phylogenetic analyses showed that all of the nine ELPs investigated were most closely related to proteins found either in eukaryotes or in bacteria that can live in association with eukaryotes. ELPs were then recombinantly expressed in Escherichia coli and exposed to the amoeba Acanthamoeba castellanii, which is functionally analogous to phagocytic cells in sponges. Phagocytosis assays with E. coli containing three ELP classes (AR, TPR‐SEL1 and NHL) showed a significantly higher percentage of amoeba containing bacteria and average number of intracellular bacteria per amoeba when compared to negative controls. The result that various classes of ELPs found in symbionts of different sponges can modulate phagocytosis indicates that they have a broader function in mediating bacteria–sponge interactions.